The Effectiveness of Audio Media in Enhancing Farmers’ Knowledge: The Case of Smallholder Banana Farmers in Western Uganda - Mark Kaahwa (International Journal of Recent Contributions from Engineering, Science & IT, 2019)
Although audio media has been presented by previous research as a suitable medium for conveying agricultural information, there is limited research in assessing its effectiveness in assisting farmers’ gain agricultural knowledge. This study thus undertook to carry out that investigation by involving 1000 smallholder banana farmers in the study which involved a baseline survey, an intervention, and an end line survey. The preliminary survey results showed that 456 farmers had relevant knowledge of farming practices and were removed from the study. However, 541 farmers were lacking the required knowledge regarding proper banana farming practices. This group was assigned to an intervention of radio broadcasts for one month. All broadcasted content was recorded on CDs and circulated to the participants for continued revision. This was followed by the end line survey and the two datasets were compared to establish the change in knowledge levels of the farmers. The tests of variances before the intervention and after the intervention indicated that the two groups being compared are assumed to be approximately equal (p >0.05). Results showed a significant difference in the mean knowledge scores before and after the intervention. Furthermore, independent t-test results reveal a statistically significant difference in the pre- and post-knowledge tests of farmers. In addition, results from Pearson Correlations show that farmers’ characteristics such as age, gender, and level of education do not influence the uptake of knowledge on farming practices by farmers. However, results reveal a statistically significant association between the source of information (Radio Broadcast & audio CDs) and knowledge gain regarding most banana farming practices by farmers. This study provides further evidence that audio media in the form of radio broadcasts and audio CDs is a vital source for agricultural information to the rural farmers. Moreover, it can be concluded that farmers’ characteristics do not influence knowledge gain for banana farming practices when audio media is used as a medium of information dissemination. And thus, audio media remains a vital source of information for resource-poor farmers and can greatly enhance their agricultural knowledge when audio media is used as an intervention.